Facile microwave synthesis of ScPO4·2H2O flowerlike superstructures: morphology control, electronic structure and multicolor tunable luminescent properties. Issue 38 (20th September 2017) - Xu, Hualan; Xu, Bo; Liu, Ran; Li, Xinwei; Zhang, Siqi; Ouyang, Chuying; Zhong, Shengliang
Abstract : ScP04 ·2H2 O flowerlike superstructures constructed by well-aligned nanorods were prepared and multicolor tunable emission including white light emission was realized by adjusting the relative doping concentration. Abstract : In this paper, a fast and facile microwave method is described to prepare monoclinic ScP04 ·2H2 O flowerlike superstructures constructed by well-aligned nanorods without use of any template or surfactant. By varying the preparation parameters, such as reactant ratio, microwave power and reaction time, various morphologies, such as nanospheres, cubes and particles were obtained. The growth process of the flowerlike microstructure was also investigated. A nanorod growth and self-assembling process was involved in the formation of the flowerlike superstructure. After calcining the ScP04 ·2H2 O microflowers at 800 °C, tetragonal ScP04 with similar morphology was obtained. Tb 3+, Eu 3+, Dy 3+, Tb 3+ /Eu 3+ and Eu 3+ /Dy 3+ doped ScP04 ·2H2 O were also prepared and their photoluminescent properties investigated. By adjusting the relative doping concentration, multicolor tunable emission of green, red and blue could be realized and the decay time results reveal that energy transfer occurs. More significantly, white light could be achieved in a 3% Eu 3+ and 2% Dy 3+ co-doped ScP04 ·2H2 O. First-principles calculations were carried out to study the structural and electronic properties, which were in accordance with the experimental observations.